Peran Kelompok Nelayan Dalam Aktivitas Pariwisata Di Desa Kedonganan Kuta, Bali - Sihombing, Lisbet; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i02.p17, 2018)
This research is motivated by the important roles of the Kedonganan people to gather in a fishing group community to develop of tourism activit y in Kedonganan Beach. F ishermen Group in Kedonganan Beach is required to become a tourism actors with many demands of tourists that visiting to Kedonganan village of F ishermen Group. The purpose of this research to find out the forms of involvement or the roles by fishermen group in supporting the tourism activit y ini Kedonganan village. T he type of data in t his study us e descriptive qualitative . Data collection techniques use in this research are interviews, study documents or literature. Techniques of informan determining use dept interviews with determining the key informan. The key informant which is selected in this study is Putra Bali’s F ishermen Group in Kedonganan village. The data analysis techniques are uing Data Reduction, Data Display , and Conclusion Drawing/Verification. The research concludes that fisherm e n group ha s an important role in tourism activity in Kedonganan village, there are in economic, social, cultural, environmental, and political. But there are problem s of the role of the fishermen in the field of the environment, because it is less in keeping it clean, the plastic waste and used garbage incinerator make bad sights and the sand starts to dirty. The fishing groups should form a section in them organizational structure that works specifically to maintain the cleanliness of the beach area. They should also add some attractions, which besides being a tourist guide who wants to see the beauty beneath the sea, the fishing activity such as knitting nets can also be used as an educational tour on marine fisheries. Thus, tourists can also invited to participate in fishing activity, and diving to study marine tourism, and preservation .   Keywords : Comunity Based Tourism (CBT), Fishermen Group, Role of Fishermen Group